Down the road from Winesburg: The spatiotemporal aesthetics of the short story sequence in Donald Ray Pollock's Knockemstiff and Laura Hendrie's Stygo. Issue 2 (1st October 2013) - Luscher, Robert M.
Two contemporary examples of the short story sequence indebted to Sherwood Anderson's influential Winesburg, Ohio – Donald Ray Pollock's Knockemstiff and Laurie Hendrie's Stygo – illustrate the complex spatiotemporal role of place in the short story sequence. The reader's progressive assembly of the imaginative space in these latter-day Winesburgs works in conjunction with other associative configurations to construct macrotexts from the autonomous stories, ones that challenge us to recognize the genre's formal paradox as we formulate spaces whose gaps and discontinuities reflect the nature of the communities portrayed, of existence within them, and the nature of the genre used to represent them.